2010
DOI: 10.1080/02701367.2010.10599669
|View full text |Cite
|
Sign up to set email alerts
|

Career Changes Among Physical Educators

Abstract: Physical educators experience several occupational constraints and a high risk of physical injury associated with a high attrition rate. Our investigation aimed at identifying the principal career reorientation factors among physical educators and reasons for their career changes. This research used semistructured interviews (n = 53) that were analyzed qualitatively and quantitatively. While younger teachers frequently invoked job precariousness, the more experienced teachers and those who made a transition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
9
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 12 publications
8
9
0
4
Order By: Relevance
“…The possibility to influence one's working methods and arrangements was a prerequisite for physically and mentally meaningful work. The study provided parallel results with earlier study [42], where physical problems were not observed to be a significant factor determining older teachers' career change or retirement plans. In this study, similar to the earlier studies [42] the older PE teachers explained that physical restrictions and chronic injuries still made them reflect on a career change.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The possibility to influence one's working methods and arrangements was a prerequisite for physically and mentally meaningful work. The study provided parallel results with earlier study [42], where physical problems were not observed to be a significant factor determining older teachers' career change or retirement plans. In this study, similar to the earlier studies [42] the older PE teachers explained that physical restrictions and chronic injuries still made them reflect on a career change.…”
Section: Discussionsupporting
confidence: 80%
“…The study provided parallel results with earlier study [42], where physical problems were not observed to be a significant factor determining older teachers' career change or retirement plans. In this study, similar to the earlier studies [42] the older PE teachers explained that physical restrictions and chronic injuries still made them reflect on a career change. However, while study by Bizet et al [42] Concentrated on work ability of PE teachers, this study also studied the coping methods to deal with the challenges for PE teachers.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, teachers who experience greater satisfaction appear to make the best teachers (Hung, 2012), and their students learn better (McCluney, Fallaize, & Schempp, 2018) and are more motivated (Ünlü & Filiz, 2019). Experienced PHE teachers' value job security, a task that allows for physical activity, a postive work climate and contact with students (Bizet, Laurencelle, Lemoyne, Larouche, & Trudeau, 2010). Their level of satisfaction varies from medium to high (Richards, Washburn, & Hemphill, 2017).…”
Section: Satisfactionmentioning
confidence: 99%